Philosophy of ethnoculture – ethnoculturology – ethnoculturography - V. A. Lychkovakh, (Ukrainian Cultural Studies, 2018)
The article investigates interrelation between philosophy of ethnoculture, ethnoculturology and ethnoculturography as components of modern culturological discourse. Aim of the article is to extend the idea about the structure of modern culturological knowledge and, in particular, to analyze how philosophy of ethnoculture, ethnoculturology and ethnoculturography correlate with each other. In connection with this there is an important task − to ground the notion of ethno-culturalography as a discourse of science and art, in particular the discourse in which ideas, archetypes, signatures and values of ethnoculture are represented in a figuratively-artistic form. The methodological value of philosophy of ethnoculture is revealed for the construction of conceptual paradigms and conceptual tools of ethnoculturology and culturological regional studies. The concept of ethnoculturography as representation of ethnoculture in artistic images of literature and art is entered in modern sciences about the culture for the first time. In particular, ethnographic approach to artistic creativity is analyzed on the examples of painting of well known Ukrainian artists Olha Petrova and Anatolii Furlet. The author understands ethnoculturology as synthesis of scientific artistic reflection that combines knowledge of ethnocultures with their pictorial reproduction by means of artistic and aesthetical facilities. For instance, ethnoculturography in painting requires a special type of discourse, where metaphysics, aesthetics, semiotics and chronotopes of the region are crossed with artistic vision, individual practice of the artist. In works of Anatolii Furlet it is manifested through artistic restoration of the mystic world of ancestors connected with "A Stone Grave" near Melitopol − one of the oldest monuments of world and national culture. For ethnoculturology of Olha Petrova the "spirit of nation" in its multicultural measurements was presented at the exhibition "Other Shores". Five "shores" of spiritual oecumene of the artist (France, Spain, Ukraine, Arabic East, Japan) outline ethnic horizons of her real and virtual travels in space and time of Eurasian cultures. Consequently, ethnoculturology practically becomes an original guide-book, a road sign (vade mecum) in the world of ethnocultures.
Keywords: philosophy of ethnoculture, ethnoculturology, ethnoculturography, representation of ethnoculture, artistic image, signature, archetype, Olha Petrova, Anatolii Furlet